Local anesthetic systemic toxicity after brachial plexus block with ropivacaine: a case report - A.G. Tutunnyk; N.V. Mynka; U.U. Kobelyatskyy (Medičnì Perspektivi)
The aim of this article is presentation of clinical case of local anesthetic systemic toxicity (LAST). Local anesthetic systemic toxicity is a rare but life-threatening complication. Ropivacaine is widely used for the regional blocks and rarely leads to the development of LAST. LAST may develop due to intravascular injection or high dose of ropivacaine. We present the case of 48-year-old-female (ASA I, 56 kg, and 165 cm), who underwent surgery on the right shoulder under brachial plexus block. Brachial plexus nerve block was performed by interscalene access with introduction of 40 ml of 0.75% ropivacaine (300 mg). Twenty minutes after the injection, complete sensory/motor block was achieved. Twenty-five minutes after the injection, the patient complained of numbness in the tongue, tinnitus and dizziness. During this time, her blood pressure was 132/83 mmHg, heart rate 82 beats/min. oxygen saturation 97%. No changes were observed on the ECG. Suspecting ropivacaine-induced toxicity, 50 mg of thiopental sodium followed by 2 mg of midazolam were administered for seizure prophylaxis, and supplemental oxygen was given via face mask. Patient’s state improved in 10 minutes. Ten minutes later 20% intralipid emulsion bolus during 2-3 min was administered followed by continuous infusion at a dose of0.25 ml/kg/min. Against clinical stablility and consciousness of the patient, decision was made to proceed with surgery, which was uneventful. Implementation of preventive measures can decrease the possibility for development of complications and emergency treatment can safe patient’s health and life. Preventive measures should include implementation of ultrasound nerve location guidance, individual calculation of local anesthetic dose, taking into account sex, weight, and physical status of a patient.